Conscientiousness and intrinsic motivation as predictors of learning perception and academic achievement - Cardoso, Ana Paula (2020)
This paper aims to relate conscientiousness, intrinsic motivation and perceived learning, and its direct and indirect relationships with academic achievement. An empirical study was undertaken, involving a representative sample of 1986 Portuguese high school students. A structural model reveals that conscientiousness directly and positively influences intrinsic motivation, perceived learning and academic achievement. In turn, intrinsic motivation directly and positively influences perceived learning and academic achievement. Corroborating previous studies, these findings suggest that personal factors are essential to improve student´s learning outcomes, namely academic achievement. Recommendations for teachers and school managers are addressed.